Numerical Model of Radical Photopolymerization Based on Interdiffusion - Shuhei Yoshida; Yosuke Takahata; Shuma Horiuchi; Hiroyuki Kurata; Manabu Yamamoto (International Journal of Polymer Science)
An accurate reaction model is required to analyze the characteristics of photopolymers. For this purpose, we propose a numerical model for radical photopolymerization. In the proposed model, elementary reactions such as initiation, propagation, and termination are considered, and we assume interdiffusion for each component in the material. We analyzed the diffraction characteristics of a radical photopolymer based on the proposed interdiffusion model with the beam propagation method. Moreover, we also performed hologram-recording experiments and evaluated the diffraction characteristics of the photopolymer medium. By comparing the numerical and experimental results, medium parameters such as reaction rate and diffusion coefficient can be estimated. We confirmed that the interdiffusion model can reproduce the experimental results and showed that the medium parameters affect the diffraction characteristics.